2020
DOI: 10.1002/ccr3.2691
|View full text |Cite
|
Sign up to set email alerts
|

Treating severe wounds in pediatrics with medical grade honey: A case series

Abstract: Medical grade honey (MGH) has antimicrobial and pro‐healing properties. We here demonstrate that MGH is an easily applicable, safe, and cost‐effective approach for severe wounds. The use of MGH should more often be considered to treat all kinds of pediatric wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…Honey is used for wound healing since ancient times because of its broad-spectrum antimicrobial and wound-healing activities [ 6 ]. Antibiotics replaced the use of honey, but the development of antibiotic resistance returned its use [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honey is used for wound healing since ancient times because of its broad-spectrum antimicrobial and wound-healing activities [ 6 ]. Antibiotics replaced the use of honey, but the development of antibiotic resistance returned its use [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide is formed by the enzyme glucose oxidase, which the bees add to the honey, and it catalyzes glucose in the presence of water and oxygen into gluconic acid and hydrogen peroxide (C 6 H 12 O 6 + H 2 O + O 2 → gluconic oxidase→ C 6 H 12 O 7 + H 2 O 2 ). Moreover, other molecules present in MGH also have a direct antimicrobial effect, such as phenolic compounds, flavonoids, methylglyoxal, and Bee defencin-1 [ 6 ]. Since the antimicrobial activity of MGH is based on multiple mechanisms, microorganisms are not capable of developing resistance toward MGH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MGH is strictly controlled and extensively tested honey, guaranteeing its safety and efficacy for medical purposes [19]. MGH exerts both broad-spectrum antimicrobial activity and wound-healing-promoting properties [20][21][22][23]. The main antimicrobial activities of MGH are thought to rely on the low pH, osmotic activity, production of hydrogen peroxide, and the presence of antimicrobial molecules (e.g., phytochemicals such as flavonoids).…”
Section: Introductionmentioning
confidence: 99%
“…Since the antimicrobial activity is attributed to multiple mechanisms, no resistance towards honey has been reported so far [24]. The wound-healing properties are multifaceted and mediated by creating a moist wound environment, stimulation of autolytic debridement and angiogenesis, anti-inflammatory and antioxidative activity, enhanced cell migration, proliferation, and re-epithelialization [20][21][22][23]. In a recent systematic review paper about honey in wound care, analyzing 30 randomized controlled studies, it was concluded that honey decreased the time of wound healing and was cost-effective [25].…”
Section: Introductionmentioning
confidence: 99%
“…The honey likely interacts with the local cells, stimulates them through various signaling mechanisms, and then these cells further signal to other local and migrating cells. For example, when honey is applied to a wound bed, such as an ulcer or non-healing wound, some of its' observed functions include: autolytic debridement, wound healing, inflammatory modulation and bacterial killing 12,68,69 . How all of these functions are achieved with the application of high concentrations of honey, > 50%, when it is observed in vitro that > 1% of honey is cytotoxic, supports the idea that we do not fully understand all of the mechanisms and chemicals within this "neutraceutical".…”
Section: Study Limitationsmentioning
confidence: 99%